Future for Public Service Television - Freedman, Des; Goblot, Vana (Goldsmiths Press, 2018)
Television is on the edge of both decline and rebirth. Vast technological change has brought about financial uncertainty and creative possibilities for producers, distributors and viewers. The proliferation of platforms from Amazon and Netflix to YouTube and the vlogosphere means extreme competition for audiences traditionally dominated by legacy broadcasters.